THE HYGIENIC EFFICIENCY OF INDIVIDUAL PROTECTIVE AND PREVENTIVE MEASURES FOR TRAFFIC POLICE OFFICERS WORKING IN HOT CLIMATES (British Journal of Global Ecology and Sustainable Development, 2025)
The article analyzes the hygienic efficiency of individual protective and preventive measures used to reduce the impact of thermal factors on the health of traffic police officers working in hot climate conditions. The study involved 120 officers serving in the Tashkent and Kashkadarya regions during 2023–2024. The results showed that the use of modern heat-resistant uniforms, cooling pads, ultraviolet-filtering glasses, and electrolyte solutions reduced the incidence of heat stress cases by 38%. The article proposes a set of complex preventive measures based on the principles of thermal hygiene.